Administering esomeprazole subcutaneously via a syringe driver in the palliative demographic: A case series. (27th December 2021) - Hindmarsh, Jonathan; Adelaja, Mercy; Abd Latif, Saiful; Lee, Mark; Pickard, Jonathan
Abstract: What is known and objective: Proton pump inhibitors are potent suppressors of gastric acid secretion, and are commonly prescribed in palliative medicine. Despite multiple relevant indications in patients at the end‐of‐life, their use is often precluded as oral and intravenous administration is frequently inappropriate or not possible. Limited anecdotal evidence suggests proton pump inhibitors may be administered subcutaneously. Our objective was to investigate the tolerability and effectiveness of the administration of esomeprazole as a continuous subcutaneous infusion over 24 h via a syringe driver. Methods: Case series ( n = 7) design assessing sequential patients admitted to a specialist inpatient centre for palliative care, who required parenteral proton pump inhibitor therapy. Results and Discussion: Four patients reported complete resolution of dyspeptic and reflux symptoms post commencement of esomeprazole. Two patients developed upper gastrointestinal bleeding, which via observation of vomitus and stools, resolved with the initiation of esomeprazole. A single patient, deemed high risk of gastrointestinal bleeding, was commenced on esomeprazole and no bleeding events occurred. What is new and conclusion: Esomeprazole when administered via a syringe driver over 24 h appears well tolerated and effective for the symptomatic management of dyspepsia and treatment of gastrointestinal bleeding. Overall, this series adds to the limited evidence base for using subcutaneous proton pump inhibitors in the palliative demographic. Abstract : Esomeprazole when administered via a syringe driver over 24 hours appears well tolerated and effective for the prophylaxis of gastrointestinal bleeding, prevention of re‐bleeding, and for the symptomatic management of both dyspepsia, and reflux. Overall, this series adds to the limited evidence base for using subcutaneous proton pump inhibitors in the palliative demographic.